The Crossing Speed of Elderly Pedestrians - Trpković, Ana; Milenković, Marina; Vujanić, Milan; Stanić, Branimir; Glavić, Draženko (Promet - Traffic&Transportation, 2017)
The population of elderly people is rapidly growing and in terms of safety, senior pedestrians represent one of the most vulnerable group. The pedestrian crossing speed is a significant input parameter in traffic engineering, which can have effect on pedestrians’ safety, especially of older population. The objective of this study was to determine the value of the crossing speed of elderly pedestrians (65+) for different types of urban crossings. The research was conducted at ten intersections in the city of Belgrade, Serbia, using the method of direct observation and a questionnaire for collecting data. The data were analysed in the statistical software package IBM SPSS Statistics. The results showed that elderly pedestrians walk slower and the crossing type significantly influenced the speed of older population. The order of crossing types in relation to the measured speed is ranked as follows, from the lowest to the highest speed value: unsignalized, signalized, signalized with pedestrian countdown display, signalized with pedestrian island and pedestrian countdown display and finally signalized crossing with pedestrian island. According to the questionnaire results, the elderly recognize the importance of implementing pedestrian counters. This indicates the necessity to provide safe street crossing for the elderly using the corresponding engineering measures.